Sexually Transmitted Infections in HIV-Infected Adults and Special Populations : A Clinical Guide - Bachmann, Laura Hinkle (Springer International Publishing : Imprint: Springer, 2017)
Though recent breakthroughs in research advance care with each day, the population of HIV-infected individuals continues to grow globally, leaving them particularly susceptible to additional STDs that are complicated by their immunocompromised state. This text is the only book to provide a comprehensive and state-of-the-art review of issues relevant to STI care in the HIV-infected adult, adolescent, and transgendered populations. Written by experts in the field, HIV in HIV-Infected Adults and Adolescents approaches these unique needs through its review of sexual history, synergies between STIs and HIV, epidemiology, issues specific for HIV-infected individuals, clinical presentation, diagnosis and management considerations for ten common STIs, and prevention strategies. Each topic includes a case-based presentation and the most current CDC-recommended STI treatment regimens. Sexually Transmitted Infections in HIV-Infected Adults and Special Populations is the ultimate resource for any physician treating adults and special populations with HIV, including HIV clinicians, sexual health specialists, general internists, family medicine practitioners, infectious diseases specialists, advanced practice clinicians, and physicians.
Keywords: Medicine.; General practice (Medicine).; Gynecology.; Public health.; Infectious diseases.; Reproductive medicine.; elektronické knihy; electronic books